24-Hour Urinary Sodium and Potassium Excretion and Cardiovascular Risk - Ma, Yuan; He, Feng J; Sun, Qi; Yuan, Changzheng; Kieneker, Lyanne M; Curhan, Gary C; MacGregor, Graham A; Bakker, Stephan J.L; Campbell, Norm R.C; Wang, Molin; Rimm, Eric B; Manson, JoAnn E; et al. (The New England journal of medicine, 2022)
The relation between sodium intake and cardiovascular disease is controversial. This study used individual-participant data from six prospective cohorts of healthy adults. Higher sodium and lower potassium intakes, estimated from multiple 24-hour urine samples, were associated in a dose-dependent manner with a higher cardiovascular risk.